Agresivitatea şi violenţa în şcolile din România: bullying şi mobbying - Bonea, Georgiana Virginia (Calitatea Vieții, 2019)
The present study starts from the identification and analysis of the phenomenology and the causality of aggression and violence in school in order to discover new simple but effective ways of preventing and combating this problem faced by both Romania and many other states of the world. Thus, starting from the existing social policies and from the official statistics provided by the Ministry of National Education, a realistic analysis of this phenomenon can be made. The issue of violence in school can no longer be ignored, as it is a serious violation of Human Rights. In such a context, governmental, institutional, social, school and family efforts are required for a more effective and lasting response. At the same time, the causes of violence in school are identified, thus providing possible solutions for preventing and combating the problem, with openings for new future analysis.